MR Spectroscopy in Sinus Mucocele: N-Acetyl Mimics of Brain N-Acetylaspartate - Andre, E.; Xu, M.; Yang, D.; Siow, J.K.; Yeo, T.T.; Xu, Y.; Lim, C.C.T. (American Journal of Neuroradiology, 2006)
SUMMARY: We describe MR spectroscopy in 2 patients with frontal sinus mucoceles that showed a dominant metabolite peak at 2.0-ppm chemical shift, simulating N-acetylaspartate (NAA) of normal neuronal tissue. In vitro analysis of postsurgical mucocele samples confirmed that the signal at 2.0 ppm was arising from the methyl moiety of an N-acetyl compound. This is probably caused by N-acetylgalactosamine or N-acetylglucosamine, which are glycoproteins found in normal respiratory mucus produced by the paranasal sinus epithelium.